SOCIAL RESPONSIBILITY IN THE FACE OF THE GLOBAL ENVIRONMENTAL CRISIS - Chenbai, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The crisis of the spiritual sphere is the root cause of a difficulty in the mankind – biosphere interaction. Gradually, people began to realize the connection between the possibility of their existence in the future and the state of the environment. The aim and tasks are to study the phenomenon of social responsibility in an exacerbation of the crisis; clarify the meaning of the concept of "responsibility" in the context of today's realities. Research methods. The theoretical foundations of the study are the works of both foreign and domestic scientists and philosophers, which comprehensively highlight the social responsibility problem and analyze the causes of aggravation of the environmental situation in the modern world. An interdisciplinary approach aimed at creating a new ecological imperative of our time is used. Research results. With the advent of information technology, most people have gained free access to information about the state of the environment. But the dominated values only increase the tension between human demands and the possibilities of the biosphere. This state of affairs has restored researchers' interest in the problem of social responsibility as a holistic phenomenon in the context of understanding of freedom as freedom of will, action, decision-making. Discussion. Ecocentric way of life necessitates the formation of environmental ethics to act according to new rules. Solving such a task can only be done by individuals who have fully experienced planetary social responsibility for nature. Conclusion. The destruction of nature is the result of permissiveness, lack of compassion for all living things. It is necessary to start with the formation of a new environmental imperative and social responsibility at all social levels as an indicator of maturity of society.